KETERKAITAN INTANGIBLE ASSET, DEBT CONTRACT DAN EXCHANGE RATE TERHADAP TRANSFER PRICING - Marito, Sarah; Putri, Vidiyanna Rizal (Ibs Press, 2025)
The purpose of this study is to determine and analyze the effect of Intangible Asset, Debt Contract, Exchange Rate and Firm size as control variable to Transfer Pricing. The sample selection using purposive sampling method and the sample of this research are 12 Mining Multinational Companies listed in Indonesian Stock Exchange (IDX). The data are obtained from secondary data of annual report of basic and Mining companies listed in Indonesia Stock Exchange in 2014-2019. The analysis technique used in this research is binary logistic regression analysis. The hypothesis in this study is based on previous research and various other supporting theories. The results of this study indicate that the Intangible Asset is negatif significant to the transfer pricing and the rest of variables are not significant to the transfer pricing.